Biorational management of root-knot of brinjal (Solanum melongena L.) caused by Meloidogyne javanica. Issue 4 (April 2022) - Das, Sukalpa; Wadud, Md. Abdul; Chakraborty, Shila; Khokon, Md. Atiqur Rahman
Abstract: Production of brinjal ( Solanum melongena L.) is considerably reduced by infestations of root-knot nematodes (RKN). As chemical pesticides are increasingly being regulated globally, scientists are focusing on biorational management. An experiment was undertaken to screen resistant brinjal cultivars in Bangladesh against Meloidogyne javanica in a pot trial. Pot and field trials were also conducted to evaluate the efficacy and profitability of individual and combined applications of several biorational components to manage M . javanica on brinjal. Of twenty brinjal cultivars screened, cv. Noagram was found 'moderately resistant' and others were 'susceptible' to 'highly susceptible' against M . javanica . In both pot and field trials, most of the growth parameters of brinjal and reproductive parameters of M . javanica were significantly different than the control for both the individual and combined treatments of different biorational components which included cabbage, marigold, vermicompost, biogas digestate, Bacillus subtilis and Pseudomonas fluorescens . The yield was significantly higher for the combined treatments than the individual applications. The benefit-cost ratio (BCR) differed among the treatments. The highest yield (29.5 t/ha) and BCR (3.67) with the lowest reproductive factor (0.33) was obtained by the combined application of biogas digestate and B . subtilis . This is the first report on the efficiency and profitability assessment of biogas digestate in combination with a bio-agent in addressing the management of RKN, which might be very important considering the global concern of environmental pollution. The cultivar Noagram might be a potential source of resistant genes in brinjal against M. javanica . Abstract : Benefit-cost ratio (BCR), biofumigants, organic amendments, resistance screening, rhizosphere bacteria, root-knot nematode, Meloidogyne javanica .